Fifteen-minute consultation: The child with obesity. Issue 3 (8th April 2021) - Low, Allison; Parry-Okeden, Sophie; Ferguson, Elspeth Clare; Wright, Neil; Elder, Charlotte Jane
Abstract : Obesity is common among children and young people, with potential for significant clinical consequences. The physical and psychological comorbidities associated with childhood obesity persist into adult life, but many children do not have access to tailored obesity services. We present a framework for the identification, assessment and management of childhood obesity by the non-specialist. We also offer strategies to initiate discussions about weight and to communicate effectively with patients living with obesity.